Estudo da compatibilidade de atemoia ((Annona cherimola Mill. X Annona squamosa L. CV. 'THOMOSON') enxertada em araticum-de-terra-fria [Annona emarginata (Schltdl.) H. Rainer variedade terra-fria] e biribá [[Annona mucosa (Bai.) H. Rainer] - Baron, Daniel [UNESP] (2014)
Grafting is used efficiently for the commercial cultivation of fruit species, because it is necessary to ensure the genetic characteristics of productive species with the use of selected clones. Although grafting is common and widespread technique, mechanisms for compatibility in woody fruit are not well elucidated. Thus, the aim of this thesis was to study of restoring of atemoya (Annona cherimola Mill. x A.squamosa L. cv. 'Thompson') grafted onto atemoya (A. cherimola Mill. x Annona squamosa L. cv. 'Thompson'), araticum-mirim [A. emarginata (Schltdl.) H. Rainer 'variety mirim'], araticum-de-terra-fria [A. emarginata (Schltdl.) H. Rainer 'variety terra-fria'] and biribá [A. mucosa (Bail.) H. Rainer]. After grafting were evaluated gas exchange; plant growth; ionic concentration of mineral elements in the leaf and root tissues; determinations of the concentrations of phenolic compounds and peroxidase activity; UGP gene expression and enzymatic activity of UDP-glucose pyrophosphorylase (UGPase). Rootstocks modulate gas exchange by altering the carboxylation efficiency and transpiration, without, however showed favorable water economy. Changes in growth and concentrations of mineral elements in leaves and roots were also observed as a function of scion/rootstock combinations. In relation to the peroxidase activity, there was an increase in 'araticum-mirim' rootstock in relation to other species. Moreover, there were no differences in the concentrations of phenolic compounds in the grafted union, although these concentrations were higher than in rootstock. Grafting altered UGP gene expression, and the combination atemoya grafted onto 'araticum-de-terra-fria' (previously regarded as compatible combination) showed an increase in gene expression since the early stages after grafting. The results showed that there UGPase enzymatic activity, but there is no difference in this activity between different scion/ rootstock ...